Automating assessment and evaluation for a bachelor’s degree program - Mozaffar A. Chowdhury; Kazi Khaled Shams Chisty; Hasanuzzaman Tushar; Kazi Md Fahim Ahmed; Shaikh Sabbir Ahmed Waliullah (Institute of Advanced Engineering and Science, 2023)
Outcome-based education (OBE) makes learning happen and measures automating assessment and evaluation system. The objective of the study is to assess student’s learning in International Finance course and report OBE and propose strategies for continual quality improvement (CQI). In this study, a widely accepted self-developed spreadsheet used to measure course learning outcomes (CLO) and program learning outcomes (PLO) of international finance in a bachelor’s degree program of fall 2021. The method of sampling technique is purposive and a sample of 27 students have been considered for the analysis. Using direct method on specific parameters (quiz, assignment, presentation, and exams), an overall CLO attainment has been measured and compared with a targeted key performance indicators (KPI) (70% is set). Findings reveal that the first three out of five CLO have met the standard KPI. However, a CQI has been proposed for further improvement of CLO. Also, future works proposed to instrument CQI processes, engage industry experts and external OBE experts from foreign universities. Program self-assessment is mandatory for quality assurance at university and also preparation for accreditation of the program needs self-assessment. Therefore, CLO is mandatory for assessment and evaluation urgently.